(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This research illustrates two plays about the character of Doctor Faustus, the first was written by Christopher Marlowe in the 16th century, and the second play was written by Gertrude Stain in the 20th century, where she modified the original play. It is clear from the beginning that the main character, Dr. Faustus, symbolizes two characteristics; on one hand, the pride in the personality of Doctor Faustus and on the other hand deals with greed and selfishness that Doctor Faustus has. Because of these two characteristics, Dr. Faustus is ultimately destructive. The knowledge possessed by the physician far exceeded the knowledge of many men, and yet it was the desire for power and knowledge that could not have been attained by a mortal, which caused him to sacrifice his soul for Lucifer and curse himself. In the two plays, he sells himself, in the first play he sells himself to obtain supernatural powers, and in the second play he sells himself in order to obtain light. This research has three chapters, Chapter one investigated the life of the two authors Christopher Marlowe and Gertrude Stein. Then point of view of the original play THE TRAGIC HISTORY OF DOCTOR FAUSTUS. In addition, chapter two about Thrilling to nothing. Finally, chapter three about Gertrude Stein’s light the lights.